The Effect of Audio Visual Media on Student Learning Outcomes during the Pandemic: Pengaruh Media Audio Visual terhadap Hasil Belajar Siswa pada Masa Pandemi - Oktaviyan, Mochammad Reda; Tirtoni, Feri (Indonesian Journal of Education Methods Development, 2021)
This study aims to describe the existence of "The Effect of Audio Visual Media on Student Learning Outcomes During the Pandemic". This type of research uses a quantitative research approach. This study uses the One Group Pretest Posttest design. The population used in this study were all fifth grade students of SDN Kejapanan III Pasuruan, with a sample of 23 students. The data collection technique in this study used a learning outcome test, where there was a pretest (initial test) and a posttest (final test). The data obtained is then calculated using the t-test and the value obtained is t count = 5.151 > t table = 2,080 at a significant level of 5% and dk 21. The t count value is outside the acceptance of Ho, then Ho is rejected and Ha is accepted. The results of the calculation show that there is an effect of Audio Visual Media on Student Learning Outcomes during the Pandemic Period at SD Negeri Kejapanan III Pasuruan, namely 0.490 using the eta square formula.